Small-molecule-induced ERBB4 activation to treat heart failure - Julie M. T. Cools; Bo K. Goovaerts; Eline Feyen; Siel Van den Bogaert; Yile Fu; Céline Civati; Jens Van fraeyenhove; Michiel R. L. Tubeeckx; Jasper Ott; Long Nguyen; Eike M. Wülfers; Benji Van Berlo; et al. (Nature Communications, 2025)
Abstract Heart failure is a common and deadly disease requiring new treatments. The neuregulin-1/ERBB4 pathway offers cardioprotective benefits, but using recombinant neuregulin-1 as therapy has limitations due to the need for intravenous delivery and lack of receptor specificity. We hypothesize that small-molecule activation of ERBB4 could protect against heart damage and fibrosis. To test this, we conduct a screening of 10,240 compounds and identify eight structurally similar ones (EF-1 to EF-8) that induce ERBB4 dimerization, with EF-1 being the most effective. EF-1 reduces cell death and hypertrophy in cardiomyocytes and decreases collagen production in cardiac fibroblasts in an ERBB4-dependent manner. In wild-type mice, EF-1 inhibits angiotensin-II-induced fibrosis in males and females and reduces heart damage caused by doxorubicin and myocardial infarction in females, but not in Erbb4-null mice. This study shows that small-molecule ERBB4 activation is feasible and may lead to a novel class of drugs for treating heart failure.